Gallnut tannic acid alleviates gut damage induced by Salmonella pullorum in broilers by enhancing barrier function and modulating microbiota - Zou, Junjie; Luan, Hongliang; Xi, Pengyuan; Xue, Junshu; Fan, Jiahao; Zhong, Xinyi; Zhou, Xun; Song, Xu; Zhao, Xinghong; Zou, Yuanfeng; Li, Lixia; Jia, Renyong; et al. (Frontiers in Veterinary Science, 2024)
Pullorum disease (PD) is a bacterial infection caused by Salmonella pullorum (S. pullorum) that affects poultry. It is highly infectious and often fatal. Antibiotics are currently the mainstay of prophylactic and therapeutic treatments for PD, but their use can lead to the development of resistance in pathogenic bacteria and disruption of the host's intestinal flora. This experiment investigated the preventive and curative effects of tannic acid (TA) on PD by adding neomycin sulphate and varying doses of TA to the drinking water of 3-day-old chicks and infecting 9-day-old chicks with S. pullorum. The study showed that the presence of S. pullorum hindered the growth and development of chicks, disrupted the structure of the liver, jejunum, and ileum, compromised the integrity of the intestinal barrier, and caused imbalances in the intestinal microbiota. The addition of TA to drinking water has been shown to significantly reduce the presence of S. pullorum in organs, improve the structure of the liver and intestines, and enhance the expression of intestinal tight junction proteins (Claudin-1, Occludin, and ZO-1), mucin-2 (MUC-2), and protect goblet cells. TA also stimulates the generation of Th1 and Th2 cytokines and the goblet cells. In addition, TA can reduce the population of harmful bacteria, such as E. coli, in the cecum, while increasing the ratio of lactobacilli. In addition, TA can reduce the number of harmful bacteria in the cecal mucosa, including E. coli, while increasing the proportion of beneficial bacteria, such as Lactobacillus, and promoting the production of Th1 and Th2 cytokines, as well as sIgA. It is worth noting that the use of antibiotics can further damage the gut microbiota of chicks. To summarise, TA can help prevent and manage PD by improving the functionality of the intestinal barrier and microbiota. The most effective prevention and control results are achieved when TA is supplied at a concentration of 0.2%.